Examining the psychometric properties of the Columbia Speech Quality Instrument in cochlear implant users - Lalwani, Anil K.; Chun, Michael B.; Hwa, Tiffany P.; Chern, Alexander; Tian, Likun; Chen, Stephanie Y.; Stewart, Michael G.; Mancuso, Dean; Cellum, Ilana P. (Frontiers in Audiology and Otology, 2024)
Objective Although speech recognition among cochlear implant (CI) users improved over the past few decades, many still report poor speech quality. Currently, there is no validated tool to measure speech quality. The objective was to examine whether a previously validated speech quality tool is applicable in the CI population using psychometric analysis. Design Cross-sectional psychometric analysis of the Columbia Speech Quality Instrument (CSQI; previously validated in normal-hearing individuals; consists of 2 original and 7 manipulated speech clips designed to accentuate selected speech characteristics) was performed in adult English-speaking CI recipients (N = 36). Subjects rated each clip using a visual analog scale (VAS) on 14 characteristics: cartoonish/not-cartoonish, clear/unclear, like/dislike, breathy/not-breathy, smooth/rough, echo-y/not-echo-y, tinny/bassy, soothing/not-soothing, natural/unnatural, mechanical/not-mechanical, hoarse/smooth, pleasant/unpleasant, male/female, and speech-like/not-speech-like. Main outcome measures included validity, reliability, and factor structure. Results Content validity was previously confirmed during instrument design. Construct validity by item-item correlation analysis demonstrated correlation of 12/14 items with ≥1 other retained item (r ≥ 0.35, Spearman). Reliability was confirmed by internal consistency; factor analysis using two subsets selected by Scree plot and factor loading ≥0.4 demonstrated Cronbach alpha coefficients of 0.89 and 0.74 for factors 1 and 2, respectively. Tinny/bassy and male/female were the only characteristics that did not pass construct validity or internal consistency. Conclusions The CSQI has strong psychometric properties in the CI population; however, our findings support removal of tinny/bass and male/female characteristics from the final instrument prior to implementation in the CI population. The CSQI can be utilized in cochlear implantees to investigate effects of changes in speech processing strategies and postoperative outcomes with different devices.